Human Metapneumovirus (HMPV) Surge: Epidemiological Trends, Surveillance Gaps, and Mitigation Strategies - Saxena, Shubhi; Sharma, Subhi; Kumar, Gourav; Thakur, Shubham (Current Respiratory Medicine Reviews, 2025)
Human metapneumovirus has been recognized as a significant pathogen of the respiratory tract, with surge detections across regions, such as China and India. Hospitalization due to HMPV infection reportedly increased in early January 2025, mainly affecting vulnerable children and the elderly. Data suggest that there have been substantial increases in the positivity rates of HMPV, particularly during the winter months. Nearly 100% of children are likely to have been infected with HMPV by the age of five. Effective control requires the development of management strategies based on continuous surveillance, including mutation tracking through a running nomenclature, monitoring of epidemiologic trends, and assessment of pathogenicity. Current research is focused on developing vaccines, particularly bivalent formulations targeting both HMPV and RSV. This commentary underscores the need for constant vigilance and collaboration among health organizations to mitigate the global public health impact of HMPV. Recent epidemiological data highlight a significant expansion in the global spread of HMPV, with its prevalence in pediatric respiratory infections rising from 3.5% in 2022 to 8-9% in 2024, corresponding with increased circulation in the post-COVID-19 period. In India, HMPV-associated hospitalizations rose by 40% between 2023 and 2025, including three new cases reported in January 2025, two infants in Karnataka and one in Gujarat, suggesting localized transmission in previously unexposed regions.
Keywords: vaccines